Optimizing Microwave-assisted Crude Butter Extraction from Carabao Mango ( Mangifera indica ) Kernels - Casas, Edgardo V.; Comedia, Von Jansen G.; Gilbuena, Arni G; Yaptenco, Kevin F. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 27 No 2 (2015), 2015)
Carabao mangoes are among the highly produced fruit crops in the Philippines. The processing and consumption of carabao mangoes leave a significant amount of waste seeds. Mango kernel butter extracted from waste seed kernels is a potential additive to cosmetic products or as a cocoa butter substitute. This study determined the pretreatment conditions that produce optimum yield prior to the mechanical extraction of the crude butter. Moreover, this study provided a general sensory evaluation of the finished product. Microwave power (160, 500, and 850 W), microwave exposure time (2.0, 3.5, and 5.0 min), and size levels (1.5, 3.0, and 4.5 mm) were tested for their effects on the yield of the mechanically extracted crude butter in wet basis percentage. The optimization procedures resulted to optimum pretreatment conditions of 160 W, 4.25 min, and 1.5 mm. Size level was the most significant factor in the crude butter yield. Sensory evaluation of the crude butter extracted at optimum pretreatment conditions through acceptance test by a test panel resulted to below neutral scores in visual appearance and odor, and above neutral score in texture, indicating the potential of mango butter as a good substitute to cocoa butter in cosmetic products. Keywords: Microwave-assisted crude butter extraction from Carabao mango kernels, optimization LAYMAN’S ABSTRACT This paper discusses the microwave-assisted mechanical screw extraction of mango butter from waste carabao mango seed kernels resulting from the processing and consumption of carabao mangoes. Moreover, the physical proper ties of the extracted butter, as well as its sensory properties as evaluated by the sensory taste panel, were also examined. The study explored the effects of the following on the microwave-assisted screw pressing of mango seed kernels: microwave power (160, 500, and 850 W), exposure time (2.0, 3.5, and 5.0 min), and size levels (1.5, 3.0, and 4.5 mm). The optimum extraction conditions were identif ied by the RSM methodology as 160 W, 4.25 min, and 1.5 mm. Sensory evaluation of the mango butter determined that it has a high overall acceptability as a substitute to cocoa butter in pharmaceutical, cosmetic, and skin care products.